2019
DOI: 10.1016/j.cjca.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Improving Statin Noncompliance: If You Build It, Will They Come?

Abstract: See article by Chen et al., pages 884e891 of this issue. Few things are as certain in cardiology as the knowledge that statins reduce cardiovascular (CV) events in at-risk individuals. Statins have significantly reduced the risk of death, myocardial infarction, stroke, and the need for coronary revascularization in dozens of high-quality clinical trials. 1 Risk reduction is proportional to low-density lipoprotein cholesterol (LDL-C) lowering; specifically, each 1 mmol/L reduction in LDL-C lowers CV events by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To improve actionability, educational materials should aim to address known barriers to statin adherence such as cost and patient apprehension regarding adverse effects. 58 , 59 , 60 As per the PEMAT, 43 other general strategies for improving actionability are to (1) address the user directly, (2) provide tangible tools such as planners or checklists to help users track their progress, and (3) explain how to use charts and diagrams included in the material to help the user take action.…”
Section: Discussionmentioning
confidence: 99%
“…To improve actionability, educational materials should aim to address known barriers to statin adherence such as cost and patient apprehension regarding adverse effects. 58 , 59 , 60 As per the PEMAT, 43 other general strategies for improving actionability are to (1) address the user directly, (2) provide tangible tools such as planners or checklists to help users track their progress, and (3) explain how to use charts and diagrams included in the material to help the user take action.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are a class of medications commonly used to reduce the level of low-density lipoprotein, sometimes referred to as "bad" cholesterol, and have been shown to reduce the risk of first (i.e., primary prevention) and recurrent (i.e., secondary prevention) cardiac events in high-risk middleaged adults by about 25% (Cholesterol Treatment Trialists' Collaborators 20052010. Despite the well-established benefit of cholesterol-lowering statin therapy and frequently touted reputation as the "wonder drug" for CVD prevention, therapeutic cholesterol management by means of statin prescribing and adherence remains suboptimal in both Canada and the United States (Hennessy et al 2016;Sparrow et al 2019aSparrow et al , 2019b. For instance, patients who are eligible for statin therapy often report never being offered statins by their physician or report discontinuing their therapy due to perceptions and fear of side effects (Bradley et al 2019).…”
Section: The Issuementioning
confidence: 99%
“…We read the important work by Chen et al, 1 which reported that 40% of patients in Alberta prescribed statins were considered nonadherent. Like the editorial published in the same issue, 2 we would like to expand this discussion by highlighting patient-focused approaches to address statin nonadherence.…”
Section: To the Editormentioning
confidence: 99%